Análise de polimorfismo nos genes do receptor de estrogênio alpha – ERα (HaeIII e MspI) em mulheres em terapia substitutiva com estrogênios - Taborda, Ana Maria de Oliveira [UNIFESP] (2014)
Introduction: The increase of the life expectancy in the last 60 years, makes women spend one-third of their lifetime in climacteric period. The hormonal replacement in the post-menopause, seems to bring many benefits such as improvement of the vasomotor symptoms, cardiovascular protection, lost bone mass prevention, improvement of urogenital atrophy and lipidic profile and, among others. Studies have been demonstrated that some of genetic components, and mineral bone density could be, at least, accessed by detection of some genetic polymorphims such as those present at estrogen, progesterone and, vitamin D receptor. Objective: To evaluate genetic polymorphisms that could be eventually associated to hormone replacement responding to conjugated estrogen equine and its relationship to mineral bone density and FSH and LH hormone in menopause. Methods: The PCR-RFLP technique was determined to detect the presence of Estrogen Receptor Alpha (ER?) - HaeIII (Íntron 1) and MspI (Éxon 1) polymorphisms. Results: The ER? HaeIII and MspI sites gene polymorphisms, inhibited the bone mass increase after hormonal therapy (p=0.001). The HaeIII polypmorphism is related to inhibitory initial levels of FSH, before hormone replacement, whereas MspI is related to estimulatory production of FSH (p=0,000). After hormone replacement, there was an increase of FSH production in patients with HaeIII (p=0,000). The LH levels observed were the same of those FSH, i.e., the HaeIII polymorphism is related to inhibitory production of LH and, MspI polymorphism is related to estimulatory production of this (p=0,000). The women with at least one polymorphic allele HaeIII and did not to hormonal replacement suffered decline of LH and FSH production (p=0,000). Conclusion: The ER? polymorphisms HaeIII and MspI, play a major role in hormone replacement therapy.